Does Accrual Accounting Reduce Public Investment? Evidence from Three Recent Evaluation Studies - Désirée I. Christofzik; Florian Dorn; Stefanie Gäbler; Christian Raffer; Felix Rösel (Wirtschaftsdienst)
Abstract International organisations push for accrual accounting in the public sector. Accrual budgets should reveal the depreciation of public capital stocks and uncover implicit debt liabilities. Three recent studies evaluated the effect of accrual accounting in German local governments — with surprising key findings. Local governments using accrual accounting reduce sales of public assets but also reduce capital spending. Those new findings cast doubt about whether accrual accounting really fosters more sustainable budgeting.